Moderasi Manajemen Laba Pada Hubungan Akrual Diskresioner Terhadap Kualitas Laba - Fitriana, Nur; Samsiah, Siti (CV. ITTC INDONESIA, 2022)
This research is a quantitative study with the quality of profit as a dependent variable. This study examines the effect of discretionary accrual relationships on the quality of profit directly and moderated by profit management. The research sample is a contractor company in Pekanbaru Riau. The results showed that discretionary accruals do not have a direct influence on the quality of profits, but after the moderation of profit management, the quality of profits can affect the quality of profits